Visible light responsive donor-acceptor stenhouse adducts with indoline-tri/tetra-phenylethylene chromophore: Synthesis, aggregation-induced emission, photochromism and solvent dependence effect. (July 2020) - Yan, Qinghua; Li, Chengpeng; Wang, Sheng; Lin, Ziwei; Yan, Qing; Cao, Derong
Abstract: We designed and synthesized two new visible light triggered photochromic and aggregation-induced emission compound derived from the third generation donor−acceptor Stenhouse adducts (DASAs) with indoline-tri/tetra-phenylethylene moiety (abbreviation: SPE-IF/TPE-IF ). The chemical structures of these compounds are identified by NMR, MS and so on. The key intermediate SPE-ID/TPE-ID as donor showed excellent AIE properties in water-THF (v/v) solutions. The absorption and emission of SPE-IF/TPE-IF were investigated by UV–Vis and fluorescence spectroscopy, respectively. The results shown they exhibited photochromic with fatigue resistance and fluorescent switching properties with visible light regulation. The open/colored triene and closed/colorless cyclopentenone isomers of SPE-IF/TPE-IF were equipped with high photo bleaching and fluorescence effect upon alternating visible light irradiation and heating both in solution and in PMMA doped solid state. And the solvent dependence effect of TPE-IF was studied. The photochromic mechanism of SPE-IF/TPE-IF was also basically investigated by computational method. These results indicate SPE-IF or TPE-IF is a promising candidate for visible light-responsive smart materials. Graphical abstract: Image 1 Highlights: The third generation DASAs with AIE including SPE-IF/TPE-IF were synthesized. The fluorescence switching of SPE-IF/TPE-IF was investigated both in solvent and doped in PMMA film. The equilibration kinetics and solvent effect of the TPE-IF were studied.